POLA MANAJEMEN PEMELIHARAAN TERNAK KAMBING KACANG DI INDONESIA : LITERATUR RIVIEW - Suryantiana Bude; Yohanes Freadyanus Kasi; Kristiana Lali Kadju (Jurnal Inspirasi Peternakan, 2026)
Kacang goats are a local Indonesian livestock species with high adaptability and play a significant role in increasing farmers' income. Goat productivity is strongly influenced by farmer management practices. The purpose of this study was to review and analyze existing research on kacang goat management practices. The method used was a literature review (journal review) by examining various research findings related to kacang goat management. The results showed that good management practices, including feeding, housing, livestock health management, and the implementation of a good reproductive system, have a positive influence on increasing kacang goat productivity. This increase in productivity is indicated by increased weight gain, high birth rates, and low mortality rates. Based on the results of various journal reviews, it can be concluded that extensive research on kacang goat management patterns has been conducted. Further research is needed to identify these patterns in Nagekeo Regency.